2019
DOI: 10.1002/lary.27794
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal mask versus intubation for adenoidectomies in children: Analysis of 1,500 operations

Abstract: Objectives/Hypothesis: To evaluate whether endotracheal intubations are superior to the use of laryngeal masks in the airway management for adenoidectomies in pediatric patients in terms of safety and duration of surgery.Study Design: Retrospective case series. Methods: A retrospective analysis of 1,500 adenoidectomies in children using laryngeal mask or endotracheal intubation for intraoperative ventilation between 2009 and 2017. Data collected included complications, duration of surgery, and duration of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…However, there was a study by Gehrke et al in which the authors retrospectively analyzed pediatric adenotonsillectomy in around 1500 patients (683 in the LMA group and 849 in the ETT group) [ 38 ]. The authors reported that in at least 10 percent of cases, LMA was replaced with ETT and that the complications were more in the LMA group than ETT group.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a study by Gehrke et al in which the authors retrospectively analyzed pediatric adenotonsillectomy in around 1500 patients (683 in the LMA group and 849 in the ETT group) [ 38 ]. The authors reported that in at least 10 percent of cases, LMA was replaced with ETT and that the complications were more in the LMA group than ETT group.…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia with tracheal intubation is the primary method used in nasal endoscopic surgery. Patients are sedated with intravenous infusion of general anesthesia drugs such as propofol to induce sleep [18][19][20]. However, due to the limited operating space in nasal endoscopic surgery and the highly vascularized nasal mucosa, intraoperative bleeding is common, which can compromise visibility of the surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…have made it more common to use (Lee et al, 1993;Pennant and White, 1993;Gehrke et al, 2019). LM placement causes less subglottic stress than standard ETT placement.…”
Section: )mentioning
confidence: 99%